SOCIAL OVERHEAD CAPITAL DAN KESEJAHTERAAN MASYARAKAT DI WILAYAH PENGEMBANGAN PROVINSI PAPUA BAGIAN SELATAN - Romualdus Turu Putra Maro Djanggo (Faculty Of Economics and Business, Musamus University, 2018)
Social Overhead Capital and Society Prosperity in Development Region of South Part of Papua Province. This Research aim to explain the development of road infrastructure, air and sea transportation infrastructure, economic infrastructure, agriculture infrastructure, education infrastructure, and health infrastructure which have shown the vary pictures to improve society prosperity and economic growth. This research use quantitative approach within descriptive analysis method. The analysed data is the secondary of time series data by the year 2005-2014. The source of seconcary data is the infrastructure development data within their indicators in BPS of four regency of Papua Province. Result of research indicate that road infrastructure, air and sea transportation infrastructure, agriculture infrastructure with irrigation channel indicator, economic infrastructure within traditional market indicator, and education infrastructure have shown positive effect to society prosperity, but do not show the positive effect to economics growth. Health infrastructure have shown the positive effect to society prosperity. Economic growth do not show the positive effect to society prosperity. Keywords: social overhead capital, infrastructure, society prosperity